G4: Assessment of the impact of anticipated external drivers of change on water resources of the coastal zone - Khan, Mohammed Zahir-ul Haque (2011)
This project will address the important external drivers that influence water resources of the coastal zone and to assess the anticipated changes in flooding, drainage congestions, salinity intrusion, water availability, sedimentation and risk of inundation of cyclone induced storm surge as a consequence of these drivers. The water resources in the coastal zone of the Ganges basin are vital for crop production, ecosystem sustenance and livelihoods. These resources are largely shaped by tidal dynamics and upstream flows, and are affected by changes in the natural, socio-economic and institutional systems. It is important to identify and prioritize these drivers, and assess their effects on water resources towards building resilient water governance and management to cope with the projected future conditions. Key activities of the project are: review of the existing model studies, literature, available data and collection of data; identification and ranking of external drivers; adaptation, calibration and validation of Soil Water Assessment Tool (SWAT) and Water Evaluation And Planning System (WEAP) models for assessing baseline hydrological conditions; setup, calibration and validation of Ganga-Brahmaputra-Meghna (GBM) basin model, South West Regional Model (SWRM), and Bay of Bengal (BoB) model; assessment of water flow pattern, salinity distribution, storm surge risk, sedimentation pattern in baseline and projected conditions; assessment of adaptation strategies to changes caused by key drivers; and exploration of policy implications for adaptation strategies and water governance. Key outputs of the project include: list of key external drivers; climate change projections for the study region; projection of scenarios for land-use and climate change; flow availability; salinity zoning map of the coastal Ganges; flood depth-duration map; water storage volume inside polders; storm surge risk map; sedimentation rate in peripheral rivers; plan for improvement of khal system, sluices and embankments; operation rules for sluices.